A study of locus of control among distance learning pursuing professional in Bangalore. (2nd December 2014) - Choudhary, Nita; Sudarshan, S.; Singh, Niranjan Kumar
Locus of control developed by Rotter (1954) is considered to be an important aspect of personality. One's 'locus' can either be internal (the person believes that they control their life) or external (the person believe that their environment, some higher power, or other people control their decisions and their life). This paper aims to study the locus of control of men and women employed in various sectors (mainly IT) at executive level and studying MBA in distance learning unit of Sikkim Manipal University of Health, Medical and Technological Sciences. For conducting this study, Rotter's scale was used having 23 items with two options 'a' and 'b'. This study consisted of total of 74 respondents, consisting of 54 male and 20 female employed in Bangalore. The results obtained after analysis support the conclusion that men are more internal than women and believe that events result primarily from their own behaviour and actions.